The role of the expression of MMP-9 and eIF4E in squamous cell carcinoma of the tongue and floor of the mouth - Golusiński, Paweł; Golusiński, Wojciech; Waśniewska, Elżbieta; Olofsson, Jan; Majewski, Przemysław; Kluk, Andrzej (Contemporary Oncology/Współczesna Onkologia, 2008)
Introduction: The high invasiveness of the squamous cell carcinoma of the tongue and floor of the mouth is caused by its ability to metastasize to the local lymph nodes and high local recurrence rate. These two factors are responsible for the poor prognosis. Aim of the study: The objective of this study was to analyze twenty nine cases of squamous cell carcinoma of the tongue and floor of the mouth and comparison the results of immunohistochemical stainings for MMP9 and eIF4E with the clinical data concerning metastases and the standard pathological techniques of tumor evaluation. Material and methods: The material comprised of formalin fixed, paraffin embedded tumor tissue of 29 oral cancer patients who underwent radical, primary surgery. Sixteen tumors were extracted from the free part of the tongue, four from the base of the tongue and nine from the floor of the mouth. The immunohistochemical stainings were preformed with a use of avidin-biotin method. The Fisher-Freeman--Halton test was used for statistical analysis. Results: Statistically significant associations were found between the number of stained cells(p=0.0306) and the staining intensity (p=0.0415) for MMP-9 and the metastases to the local lymph nodes. The staining intensity for eIF4E did not reach the level of statistical significance (p=0.8924). The analysis comparing local recurrence with MMP-9 and eIF4E expression, demonstrated as the number of stained cells and the staining intensity, did not reveal statistically significant associations (MMP-9: number of stained cells p=0.5757, staining intensity: p=0.4320; eIF4E staining intensity: p=0.5600). Conclusions: 1. The expression of MMP-9 appears to be associated with the formation of metastases to the lymph nodes. 2. It seems that immunohistochemical evaluation of the 4E expression in the primary tumor region is of no use because of high sensitivity. However, this technique may be useful for the evaluation of “pathologically clean” surgical margins.